2004
DOI: 10.1128/jvi.78.24.13613-13626.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Human Papillomaviruses Encode Four Different E5 Proteins Whose Chemistry and Phylogeny Correlate with Malignant or Benign Growth

Abstract: We performed a phylogenetic study of the E2-L2 region of human mucosal papillomaviruses (PVs) and of the proteins therein encoded. Hitherto, proteins codified in this region were known as E5 proteins. We show that many of these proteins could be spurious translations, according to phylogenetic and chemical coherence criteria between similar protein sequences. We show that there are four separate families of E5 proteins, with different characteristics of phylogeny, chemistry, and rate of evolution. For the sake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 55 publications
(93 reference statements)
2
131
0
1
Order By: Relevance
“…A recently published phylogenetic analysis based on the nucleotide sequence of the E6 proteins (37) revealed that distinct phylogenetic branches of E6 proteins can be recognized. One clade consisted out of known high-risk HPV types and included HPV70 (37).…”
Section: Cancer Epidemiology Biomarkers and Prevention 1265mentioning
confidence: 99%
“…A recently published phylogenetic analysis based on the nucleotide sequence of the E6 proteins (37) revealed that distinct phylogenetic branches of E6 proteins can be recognized. One clade consisted out of known high-risk HPV types and included HPV70 (37).…”
Section: Cancer Epidemiology Biomarkers and Prevention 1265mentioning
confidence: 99%
“…Ainsi, selon le type de papillomavirus, deux protéines virales (E5 et E8) pourraient interférer avec la régulation du zinc et favoriser l'activation de voies de signalisation impliquées dans la synthèse de facteurs de transcription essentiels pour l'expression et la répli-cation du génome viral (Figure 2). Parmi les PVH cutanés ou muqueux, les PVH du genre β se distinguent par l'absence des gènes E5 et E8 [9]. Ainsi, nos résultats viennent corroborer l'hypothèse récem-ment formulée [2] selon laquelle les PVH β, en particulier le PVH5 oncogène, sont des commensaux défectifs très répandus et asymptomatiques dans la population générale.…”
Section: Les Pvh B Des Commensaux Défectifsunclassified
“…They showed that there is a clear pattern of divergence from late to early genes at the protein level, which increased in the progression L1 < L2 < E6 ≈ E7 < E5. Among the E5 proteins from the alpha genus it was clear that there was not an evident sequence similarity and that the evolutionary divergence between present proteins rises to 80% (Bravo & Alonso, 2004). The few common characteristics for the alpha genus E5 proteins are the high hydrophobicity, the high Ile+Leu+Val content and the presence of transmembranal regions.…”
Section: Organization and Classification Of Human Papillomavirusesmentioning
confidence: 99%
“…The less conserved viral sequences from the alpha genus are those from the E5 gene, since the homology in this genus is only of 25% and 40% when only the HR-HPV types are considered. Few years ago, Bravo and Alonso (2004) described the evolutionary characteristics of the E5 proteins and compared them with the E6 and E7 oncogenic proteins and with the structural proteins L1 and L2. They showed that there is a clear pattern of divergence from late to early genes at the protein level, which increased in the progression L1 < L2 < E6 ≈ E7 < E5.…”
Section: Organization and Classification Of Human Papillomavirusesmentioning
confidence: 99%
See 1 more Smart Citation